Occupational Hazards, Injuries, and Health Outcomes Among Water and Wastewater Workers: A Systematic Review - Diana Artuso; Francesco Giacobbe; Genoveffa Giaquinta; Placido Brancato; Cinzia Lombardo; Viviana Cafiso; Caterina Ledda (Applied Sciences, 2026)
Water and wastewater workers encounter complex occupational exposures, but evidence on related injuries and adverse health outcomes remains fragmented. We systematically searched PubMed/MEDLINE, Scopus, Web of Science Core Collection, and Embase on 23 April 2026 and synthesized evidence using a Population–Exposure–Outcome framework and PRISMA 2020. Two reviewers independently screened and extracted data. Methodological quality was evaluated with design-specific Joanna Briggs Institute tools, and certainty for prevention measures was assessed using a GRADE-informed narrative approach. Seventy studies published from 1940 to 2025 were included; most were cross-sectional. The most reproducible findings concerned respiratory effects from bioaerosols, endotoxins, and hydrogen sulfide, musculoskeletal morbidity (12-month low-back-pain prevalence up to 72.8%), and severe acute hazards during chemical handling and confined-space entry. Infectious findings, including hepatitis A/E, Helicobacter pylori, and intestinal parasites, were heterogeneous and particularly vulnerable to confounding by community background prevalence. Employment duration, inadequate personal protective equipment, insufficient training, and unsafe facility design amplified risk. Meta-analysis was precluded by heterogeneity, and confidence was limited by cross-sectional designs and inconsistent adjustment. The review was not registered and received no external funding. Engineering controls, confined-space safeguards, and task-specific protective equipment are priority measures, although intervention-effectiveness evidence remains low or very low certainty.